Seepage Evaluation of Mosul Earth Dam - H. Irzooki, Raad (Anbar Journal of Engineering Sciences, 2012)
The aim of the present research is studying the efficiency and performance of Mosul Dam with respect of the seepage. It was depended on the dam field observations of years 2004, 2003 and 1990. These observations included a discharge measurements and chemical analysis of seepage water from three points at the downstream left side of the dam, and the chemical analysis of reservoir water. Also, the ground water levels of grouting gallery piezometers and opening piezometers at the downstream right side were measured. All these field observations were taken with every water level of the dam reservoir. The results concluded that the dam embankments being a good efficiency with respect the seepage, however, the efficiency of the dam foundation, which presented by the grout curtain, is in a good condition in most regions, except the region limited between section (68) and (70), where the efficiency of this region is equal to (19.5%), (23.07%) and (25.55%) in years 2004, 2003 and 1990 respectively. Also, the results indicated that some sections of the grout curtain , such as section (79), being with not agreeable efficiency in 1990, where Is equal to (45.97%). But according to a continuous and intensive grouting, the efficiency of this section increased and become (73.74%) and (73%) in 2003 and 2004 respectively